2015
DOI: 10.1093/mnras/stu2731
|View full text |Cite
|
Sign up to set email alerts
|

Stellar activity as noise in exoplanet detection – II. Application to M dwarfs

Abstract: The ubiquity of M dwarf stars combined with their low masses and luminosities make them prime targets in the search for nearby, habitable exoplanets. We investigate the effects of starspot-induced radial velocity (RV) jitter on detection and characterization of planets orbiting M dwarfs. We create surface spot configurations with both random spot coverage and active regions. Synthetic stellar spectra are calculated from a given spot map, and RV measurements are obtained using cross-correlation technique. We ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 77 publications
10
34
1
Order By: Relevance
“…(Pecaut & Mamajek 2013). This corresponds to a temperature difference of ∼100-200K, which is consistent with spot temperature contrasts published for M-dwarfs of similar temperatures (Andersen & Korhonen 2015). The temperature ratio between the coolest and warmest hemispheres can also be estimated from the peak-to-trough amplitude of the K2 light curve and the Stefan-Boltzmann law: ( ) consistent with the temperature difference estimated from the -¢ V i variability amplitude.…”
Section: Archival and Follow-up Photometric Monitoringsupporting
confidence: 87%
“…(Pecaut & Mamajek 2013). This corresponds to a temperature difference of ∼100-200K, which is consistent with spot temperature contrasts published for M-dwarfs of similar temperatures (Andersen & Korhonen 2015). The temperature ratio between the coolest and warmest hemispheres can also be estimated from the peak-to-trough amplitude of the K2 light curve and the Stefan-Boltzmann law: ( ) consistent with the temperature difference estimated from the -¢ V i variability amplitude.…”
Section: Archival and Follow-up Photometric Monitoringsupporting
confidence: 87%
“…This tendency needs to be examined in a larger sample with new spectropolarimetric surveys of moderately active M dwarfs. Besides, given that surface spot distributions are significantly impacting our ability at detecting Earth-like planets (see, e.g., simulations done by Andersen & Korhonen 2015), it will be worthwhile to extent this study to later-type M dwarfs to improve our knowledge of their spot patterns. For example, the Doppler Imaging is a powerful tool to investigate whether spot patterns change and, e.g., evolve towards more even distributions of smaller features, when going from partially to fully convective stars.…”
Section: Photosphere Occupancymentioning
confidence: 99%
“…Starspots on a rotating photosphere can introduce radial velocity variations (e.g., Andersen & Korhonen 2015). Gagné et al (2016) investigated the effect of starspots on radial velocity measurements and found that an active star shows a long-term radial velocity variation of 25-50 m s −1 in the near-infrared.…”
Section: Comparison With the Previous Publicationsmentioning
confidence: 99%